2005
DOI: 10.1016/j.pain.2005.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Persistent idiopathic facial pain exists independent of somatosensory input from the painful region: findings from quantitative sensory functions and somatotopy of the primary somatosensory cortex

Abstract: In 14 patients with unilateral persistent idiopathic facial pain (PIFP), classified according to the criteria of the International Headache Society, and 16 age-matched control subjects sensory functions were examined on the face by quantitative sensory testing (QST). Additionally, the somatotopy of the primary somatosensory cortex (SI) to tactile input from the pain area was evaluated by means of magnetoencephalography. Previously reported abnormalities in PIFP as a dishabituation of the R2 component of the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 32 publications
3
46
0
3
Order By: Relevance
“…It was found that the QST was not altered in these patients. In addition, the distance between the cortical representations of the lip and index Wnger did not diVer signiWcantly between patients and controls, suggesting that idiopathic facial pain is maintained by mechanisms which may not involve somatosensory processing of stimuli from the painful skin (Lang et al 2005).…”
Section: Introductionmentioning
confidence: 89%
“…It was found that the QST was not altered in these patients. In addition, the distance between the cortical representations of the lip and index Wnger did not diVer signiWcantly between patients and controls, suggesting that idiopathic facial pain is maintained by mechanisms which may not involve somatosensory processing of stimuli from the painful skin (Lang et al 2005).…”
Section: Introductionmentioning
confidence: 89%
“…There were 19 studies that met the inclusion criteria for the review but could not be included in the meta-analyses because raw data could not be extracted (Peters et al, 1992;Leroux et al, 1995;Knost et al, 1997;de Tommaso et al, 2000;Nappi et al, 2002;Desmeules et al, 2003;Katsarava et al, 2003;Banic et al, 2004;Lang et al, 2005;Ayzenberg et al, 2006;Carleton et al, 2006;Sandrini et al, 2006;Al-Azzawi et al, 2008;Filatova et al, 2008;Mendak et al, 2010;Neziri et al, 2010;Biurrun Manresa et al, 2013a,b;Desmeules et al, 2014). We were unable to obtain a meaningful outcome relevant to our research question for eight studies (see Table 2 for details).…”
Section: Studies Not Included In the Meta-analysesmentioning
confidence: 99%
“…For example, for five studies, the authors were unable to access their data (Peters et al, 1992;Knost et al, 1997;Nappi et al, 2002;Katsarava et al, 2003;Sandrini et al, 2006), two considered that it was inappropriate to use their data and declined to share their results (Carleton et al, 2006;Biurrun Manresa et al, 2013a,b), and the authors of nine studies did not respond to several enquiries about their data (Leroux et al, 1995;de Tommaso et al, 2000;Desmeules et al, 2003Desmeules et al, , 2014Banic et al, 2004;Lang et al, 2005;Ayzenberg et al, 2006;Al-Azzawi et al, 2008;Mendak et al, 2010). As noted in the peer review process of the current review, this does reflect a kind of bias -towards papers the authors of which are willing and able to share their data for the purposes of the meta-analysis.…”
Section: Limitationsmentioning
confidence: 99%
“…The sensory findings in the scientific literature on these conditions remain controversial 9 . PIFP does not differ from controls in quantitative sensory testing (QST) 10 , atypical facial pain showed to be a heterogeneous group 7 , and atypical odontalgia that included only patients with previous history of dental procedures as etiological factors, showing abnormal sensory processing 11 . No studies had investigated separately patients with a clear history of trauma and those with idiopathic pain and spontaneous initial about their somatosensory impairment 3 , and QST can help in the elucidation of mechanisms involved in sensory processing 12 .…”
mentioning
confidence: 93%